보편적 규정주의에 기초한 공리주의에서 개인의 개별성과 권리의 문제 - 류지한; Lyou¸ Jihan (윤리연구, 1(134), 2021)
보편적 규정주의에 기초한 공리주의는 1인칭 숙고 모델에 기초하고 있기 때문에 방법론적으로 개인의 개별성을 존중하지 않고, 이로 인해 개인에 대한 무제한적 희생과 권리 침해를 도덕적으로 용인한다고 비판받는다. 더 나아가 매키는 헤어의 보편적 규정주의 접근법이 공리주의가 아니라 개인의 개별성을 존중하는 권리 기반 도덕이 될 수도 있다고 비판한다. 이에 대해 헤어는 보편적 규정주의의 도덕적 사유가 기본적으로 개인 내적인 1인칭 숙고 형식을 띤다는 점을 인정하면서도, 이에 기초한 공리 주의가 비판적 사유에서 개인의 개별성과 차이를 충분히 고려할 수 있다고 반박한다. 또한 헤어는 그의 두 수준 공리주의가 직관적 사유에서 개인의 개별성과 불가침성에 기초한 권리를 충분히 인정하고 보호할 수 있기 때문에 역직관성 비판에서 벗어날 수 있을 뿐만 아니라 매키가 제안하는 권리 기반 도덕을 포용할 수 있다고 주장한다. 그러나 이와 같은 논박에도 불구하고 헤어의 이론은 비판적 사유에서 공리 극대화를 위하여 한 개인의 개별성과 불가침성을 제한 없이 침해할 가능성을 이론적으로 완전히 배제하지는 못한다. 이것은 윤리 이론으로서 결함으로 보인다. 헤어의 윤리 이론에서 개인의 개별성의 문제가 야기하는 역직관성은 개인 간의 윤리 문제를 개인 내적인 1인칭 숙고로 환원하는 도덕적 사유 모델 안에 그리고 반직관주의적 논증 방법 안에 내재되어 있는 것으로 보인다. 이 두 견해를 고수하는 한, 헤어 식의 공리주의는 도덕적 사유의 두 수준 이론을 수용한다고 할지라도 개인의 개별성을 침해한다는 비판으로부터 완전히 벗어날 수는 없다. 다만, 보편적 규정주의에 기초한 공리주의는 상호 의사소통과 담론의 과정을 통해서 1인칭 숙고 모델의 비판적 사유에 내재하고 있는 문제를 다소간 완화할 수 있을 것이다. Since universal prescriptivist utilitarianism is based on the first-person deliberation model about moral thinking, it methodologically does not take separateness of persons seriously, and therefore is criticized for morally allowing the unlimited sacrifice to persons and unrestricted violation of the fundamental rights. Further, in criticizing R. M. Hare, J. L. Mackie argues that the universal prescriptivist approach may be a rights-based morality that takes separateness of persons seriously rather than a utilitarian fusion of perspectives. In response to these criticisms, Hare refutes that moral thinking based on universal prescriptivism is fundamentally in the form of intrapersonal first-person deliberation, but utilitarianism based on it takes separateness and differences of persons in critical thinking. Hare also argues that his two-level utilitarianism is capable of not only escaping criticism of counterintuitiveness but also embracing the rights-based morality that Mackie proposes because it can fully endorse and protect the rights based on separateness and inviolability of persons in intuitive thinking. However, despite such refutations, Hare's theory cannot wholly exclude the possibility of infringing on the separateness and inviolability of persons without limit to maximize utility in the level of critical thinking, at least theoretically. It seems to be a flaw as an ethical theory. However, in Hare's ethical theory, the counterintuitiveness caused by the separateness of persons seems to be inherent in the moral thinking model that reduces the interpersonal ethical problem to intrapersonal first-personal deliberation and in the anti-intuitionist argumentation method. As long as he adheres to these two views, Hare's utilitarianism cannot be completely freed from the criticism that it violates the separateness of persons, even if it accepts the two-level theory of moral thinking. However, through the process of mutual communication and discourse, utilitarianism based on universal prescriptivism will be able to alleviate some of the problems inherent in the critical thinking of the first-personal deliberation model.